A review of types of feeds used in polychaetes culture - Aiman amanina, Amran; Fatimah A'tirah, Mohamad (Prince of Songkla University, 2022)
Polychaete serves as aquafeed for most aquaculture species and bioremediation agent of organic waste. Polychaete used for broodstocks of finfish and crustaceans stimulates gonadal maturation and endocrine system in penaeid shrimp, therefore overcoming the shortfall in juvenile production of animals and securing reliable production of aquaculture harvests. Commercial feed gained the highest ground in polychaete farming. Microalgae’s essential nutrients and favorable morphology are ideal for polychaete larviculture. Home made feed is unpopular due to complex structural fibre but applicable as co-feed in polychaete nourishment. High organic matter waste is competent as polychaete feed although might be lacking in adequate nutrients. The ideal feed for polychaete growth, focusing on different life stages are poorly studied. This review studies the fitness of microalgae in larviculture, nutritional value of commercial feed, home-made feed as co feed options in polychaete nourishment and bioremediation benefit on polychaete’s waste feeding behaviour.